自然縮小したfibrous dysplasiaの1例 - 安部, 裕介; 野中, 聡; 今田, 正信; 原渕, 保明; 駒林, 優樹 (Stomato-pharyngology, 2005)
A 12-year-old male with mandible fibrous dysplasia is reported. He was suffering from a swelling of the right cheek. Examinations by magnetic resonance imaging (MRI) and computed tomography (CT) revealed a mass at the ramus of mandible. Biopsy was performed and the histological examination diagnosed fibrous dysplasia. In order to avoid deformity and dysfunction of the lower jaw, we did not perform surgical resection and followed up without any treatment. After three years observation, the mass regressed spontaneously. 下顎骨に発生した12歳男児fibrous dysplasia症例を報告する.主訴は, 頬部腫脹であった.CT, MRIにおいて右下顎枝より発生する腫瘤を認めた.生検術を施行し, 病理組織学的検査の結果, fibrous dysplasiaと診断された.美容, 機能上の観点から経過観察を行った.3年間の経過観察で病変の自然縮小を認めた.